Komunitas Plankton Sungai Noemuti, Kecamatan Bikomi Selatan, Kabupaten Timor Tengah Utara - Priyambodo, Hernur Yoga; Santiari, Made; Farid Amrulloh, Mohamad Fajar; Arya Wiguna, Gede (JURNAL BIOSHELL, 2023)
Noemuti River is a river located in North Central Timor District. The river is used by local people for daily needs such as washing motorbikes and clothes. In addition, at some point it is also used to mine sand. Seeing this phenomenon, it is estimated that there has been a change in the plankton community in the river, so it is necessary to conduct research on the plankton community in the river. This research was conducted by purposive random sampling to take existing plankton samples to see their abundance, diversity, dominance and evenness using index calculations. Based on research that has been done, the Noemuti River has an abundance of plankton 11400, 8716 and 7241 cells/L. The diversity index is 2.362; 2,627; and 2,880. Dominance index 0.173; 0.121 and 0.071 and the evenness index is 0.753; 0.838 and 0.918 this shows that the Noemuti River has a moderate and relatively even distribution of plankton diversity. So it can be concluded, that activities around the Noemuti river do not really affect the existing plankton community.